Disaggregated Economic Accounts - Andersen, Asger Lau; Huber, Kilian; Johannesen, Niels; Straub, Ludwig; Vestergaard, Emil Toft (Quarterly Journal of Economics, 2026)
Abstract We develop a system of disaggregated economic accounts. The system breaks down national accounting positions into bilateral flows between consistently defined groups of consumers (consumer cells), groups of producers (producer cells), the government, and the rest of the world. We disaggregate the full circular flow of money, including consumer spending, labor compensation, firm profits, intermediates trade, foreign trade, and government transactions, while satisfying all national accounting identities. We implement the disaggregated system for small region-by-industry cells in Denmark and present stylized facts, such as variation in domestic spending, local and urban bias in consumer spending, and a pattern of triangular flows across regions. Cell-level measures of spending intensity capture how much spending by a cell contributes to the income of cells experiencing unemployment after a shock. Using a general equilibrium model, we show that fiscal transfers raise aggregate GDP by more when they target cells with high spending intensity on unemployed cells. The disaggregated economic accounts help governments select more effective policies.